Contributions of energy pathways to ATP production and pH variations in postmortem muscles. (July 2022) - Wang, Chengcheng; Matarneh, Sulaiman K.; Gerrard, David; Tan, Jinglu
Abstract: The roles of energy pathways in postmortem muscles are still debated. In this study, the contributions of different pathways to ATP production and pH variations were analyzed by using a kinetic model based on data from beef longissimus lumborum . Phosphocreatine represents over 92% of the initial ATP production but, after 24 h, glycolysis, phosphocreatine, myokinase reaction, and aerobic respiration contribute, respectively, 89.44%, 5.26%, 4.44%, and 0.86% of the cumulative amount of ATP produced. ATP hydrolysis and glycolysis result in 0.52 and 0.6 units of pH decline, respectively, at 24 h with ATP hydrolysis accounting for most of the early decline. Phosphocreatine, myokinase reaction, and aerobic respiration lead to, respectively, 0.08, 0.07, and 0.004 units of pH increase after 24 h though phosphocreatine is depleted within the first 30 min. Furthermore, electrical stimulation affects pH primarily through ATP hydrolysis and glycolysis. The initial muscle oxygen saturation level and phosphocreatine content affect pH but the influences are small.